Islamic Legal Perspectives on Rewarding Worship (Īṣāl al-Thawāb) to the Deceased: A Comparative Study of Muhammadiyah and Nahdlatul Ulama - Hamdi. R, Khairul; Day, George Soros Setiawan; Fadhlullah, Fathan; Ashufah, Abdul Hayyaqdhan (Universitas Islam Negeri Alauddin Makassar, 2025)
This study examines the contrasting legal perspectives of Muhammadiyah and Nahdlatul Ulama (NU) on the practice of bestowing the rewards of worship (īṣāl al-thawāb) to the deceased—an enduring and widespread tradition among many Indonesian Muslims. The purpose of this research is to explore the theological and methodological foundations underlying each organization's stance and to identify the broader implications of these differing views for Islamic legal discourse in Indonesia. Employing a qualitative, comparative approach, the study utilizes literature-based analysis and in-depth interviews to investigate fatwas issued by Muhammadiyah’s Tarjih Council and NU’s Bahtsul Masail. The findings reveal a sharp divergence: Muhammadiyah rejects the practice, considering it unsupported by scriptural evidence and classifying it as bid‘ah (religious innovation), while NU legitimizes the practice based on ijmaʿ (consensus), qiyās (analogy), and long-standing tradition, especially in communal rituals like tahlilan. The originality of this research lies in its focused comparison of the legal reasoning (istinbāṭ al-ḥukm) used by Indonesia’s two largest Islamic organizations, which reflects deeper epistemological tensions between scripturalist and traditionalist orientations in contemporary Islamic jurisprudence. The study has broader implications for understanding how Islamic authority is negotiated in pluralistic societies and how divergent methodologies shape religious practices at the grassroots level. These findings contribute to ongoing discussions on the role of legal pluralism, tradition, and reform in shaping Indonesian Islamic identity.